4Q147 An Amulet? - Feldman, Ariel 1974-; Feldman, Faina (2019)
Among the tefillin and mezuzot edited by Józef T. Milik in DJD 6 is 4Q147 (4QPhylactère T). Milik was unable to decipher this scroll, and it remains unpublished. This study offers a preliminary edition of 4Q147. Like many tefillin from the Judean Desert, it was written in a tiny semi-cursive script and folded. However, while tefillin contain passages from Exodus and Deuteronomy, 4Q147 features a non-scriptural text. Elaborating on God's generous provisions and evoking angelic names, this minuscule scroll might be an amulet.
Keywords: Raphael; Amulet; Angels; Apotropaic; Mezuzah; phylacteries; Tefillin